The Neoliberal Myth in Latin America: The Cases of Mexico and Argentina in the 90s - Veronica Ronchi (Fondazione Eni Enrico Mattei (FEEM), 2007)
During the 90s most Latin American countries were submitted to neoliberal structural reform policies. Neoliberal policies imposed market supremacy, reduced the States role in the economy and deregulated the markets. This paper aims at describing how these policies affected the most important macroeconomic indexes, with special emphasis on Argentina and Mexico, the two countries that suffered most from the economic crises of the 80s and 90s, and where the neoliberal policies were applied with greater orthodoxy. In spite of a slight improvement in some macroeconomic indexes, in Latin America neoliberalism failed to reduce poverty and unemployment, and was unable to guarantee a fair distribution of the wealth and improve welfare.
Keywords: E21; E22; E24; E26; N16; N26; N36; O16; 330; Latin America; Mexico; Argentina; 90s; Neoliberalism; Wirtschaftsreform; Wirtschaftsliberalismus; Lateinamerika